2018
DOI: 10.3126/ajms.v10i1.20748
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of albumin-bilirubin score, MELD and Child Pugh scores for predicting the in-hospital mortality in cirrhotic patients complicated with Upper GI bleeding in a Tertiary care hospital

Abstract: Background: Alcoholic liver Disease (ALD) encompasses a spectrum of Injury, ranging from simple steatosis to frank cirrhosis which is evaluated by many scoring systems. Aims and Objective: Our study aims at evaluating the discriminative abilities of Child-Pugh, model for end-stage liver disease (MELD), and albumin-bilirubin (ALBI) scores in predicting the inhospital mortality in cirrhotic patients complicated with acute upper gastrointestinal bleeding. Materials and Methods: Data of Patients with L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
(13 reference statements)
0
2
0
Order By: Relevance
“… 5 Being a mathematical model, it is based on routine lab parameters and does not take into account the presence or absence of ascites or encephalopathy. 6 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 5 Being a mathematical model, it is based on routine lab parameters and does not take into account the presence or absence of ascites or encephalopathy. 6 …”
Section: Discussionmentioning
confidence: 99%
“…Various studies have shown it to be a good predictor of upper GI bleed in cirrhotic patients and have found it comparable to the CTP and MELD score in predicting the in-hospital mortality. 6 …”
Section: Discussionmentioning
confidence: 99%